35.7k views
1 vote
PLZ HELP!!!!

1.Which expression is equivalent to 3 x – 3 y?


2.Rashad solved the inequality 74x10 and determined that 7x5 could equal 6. Is Rashad correct?


3.What values of 7x5 satisfy this inequality 74x9?

User Dnhyde
by
5.3k points

1 Answer

0 votes

Answer:

Expression 3x - 3y = 3 (x - y)

Explanation:

Expression equal to 3x - 3y = 3 (x-y)

- By taking 3 common from the equation

Eg : If x = 5 , y = 3

3x - 3y = 3 (5) - 3 (3) = 15 - 9 = 6

3 (x - y) = 3 ( 5 - 3 ) = 3 (2) = 6

As both above are equal, the expression equivalency is hence proven .

User Katalin
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.